(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2017)
This paper presents an adaptive control technique to control the movement of DC motor for one-DOF rehabilitation robot. Different types of controllers are used to provide accurate positioning of the motor for robots. PID controller is one of the commonly used controllers. However, one limitation of PID controller is that it is not able to adapt the variations in the load, as limb stiffness can be varied from patient to patient and PID is tuned for standard stiffness. Whenever the unknown and inaccessible load torque is imposed, the performance of the robot will be affected and it will have steady state error. Therefore, in this project a model reference adaptive controller (MRAC) is designed for the robot to reduce the positioning error and make the robot beneficial for a wide range of stroke patients. The simulated results show the designed controller is able to cope with the variations in limb’s stiffness of the patients without the aid of any additional stiffness detection sensors.